Liquidity premia, price-rent dynamics, and business cycles - Jianjun Miao; Pengfei Wang; Tao Zha (Federal Reserve Bank of Atlanta, 2014)
In the U.S. economy during the past 25 years, house prices exhibit fluctuations considerably larger than house rents, and these large fluctuations tend to move together with business cycles. We build a simple theoretical model to characterize these observations by showing the tight connection between price-rent fluctuation and the liquidity constraint faced by productive firms. After developing economic intuition for this result, we estimate a medium-scale dynamic general equilibrium model to assess the empirical importance of the role the price-rent fluctuation plays in the business cycle. According to our estimation, a shock that drives most of the price-rent fluctuation explains 30 percent of output fluctuation over a six-year horizon.
Keywords: E22; E32; E44; 330; asset pricing; financial frictions; working capital; cutoff productivity; heterogeneous firms; endogenous TFP; house price; liquidity constraint